Diagnostic value of immunohistochemistry for the detection of the BRAFV600E mutation in primary lung adenocarcinoma Caucasian patients - Ilie, Marius I.; Long, E.; Hofman, V.; Dadone, B.; Marquette, C. H.; Mouroux, J.; Vignaud, J. M.; Begueret, H.; Merlio, J. P.; Capper, David; Deimling, Andreas von; Emile, J. F.; et al. (Annals of oncology, 2013)
Background - Non-small-cell lung carcinoma (NSCLC) patients with a BRAFV600E mutation benefit from targeted therapy. The usefulness of immunohistochemistry (IHC) as an alternative approach for the detection of BRAFV600E in NSCLC patients has not been evaluated until now. This study compared the specificity and sensitivity of IHC with other methods for the detection of BRAFV600E in primary lung adenocarcinoma. - Patients and methods - BRAF mutations were analysed by DNA sequencing of a Caucasian subpopulation of selected 450 of 1509 (30%) EGFR, KRAS, PI3KA, Her2 and EML4-ALK wild-type (wt) primary lung adenocarcinomas. Detection of the BRAFV600E mutation was carried out by IHC using the VE1 clone antibody and compared with the results of other molecular methodologies. - Results - Of 450 (9%) of tumours, 40 harboured a BRAF mutation, which corresponded to either a BRAFV600E or a non-BRAFV600E mutation in 21 of 450 (5%) and 19 of 450 (4%) cases, respectively. The IHC VE1 assay was positive in 19 of 21 (90%) BRAFV600E-mutated tumours and negative in all BRAFnonV600E-mutated tumours. - Conclusion - IHC using the VE1 clone is a specific and sensitive method for the detection of BRAFV600E and may be an alternative to molecular biology for the detection of mutations in NSCLC.
Gesehen am 17.03.2021
Im Titel ist "V600E" hochgestellt
First published: 6 November 2012